University students’ perspectives on Artificial Intelligence: A survey of attitudes and awareness among Interior Architecture students - Cao, Yujie; Aziz, Azhan Abdul; Arshard, Wan Nur Rukiah Mohd (IJERI: International Journal of Educational Research and Innovation, 2023)
This study explores interior architecture students’ perspectives on artificial intelligence (AI) technologies and their implications for future career prospects. A survey of 230 third-year interior architecture students in China utilized a Technology Acceptance Model (TAM)-based questionnaire, yielding 158 valid responses. The investigation aimed to gauge students’ familiarity with recent AI advancements (e.g., ChatGPT, Stable Diffusion, Midjourney) and their readiness to incorporate AI into their future careers. Findings unveiled limited awareness of cutting-edge AI technologies and concerns about AI’s impact on employment opportunities. Nonetheless, students exhibited receptiveness to integrating AI for enhanced productivity and creativity. The structural equation modeling verified TAM’s efficacy in forecasting students’ AI acceptance intentions, highlighting perceived usefulness and ease of use as pivotal factors. The study’s insights offer guidance for educational institutions to cultivate emerging technology competence among students, enabling them to excel in a design industry undergoing AI-driven transformations. The study’s contribution lies in the application of TAM to evaluate AI acceptance within the distinct domain of interior design education.